If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 96 = 3(4x + -8) Reorder the terms: 96 = 3(-8 + 4x) 96 = (-8 * 3 + 4x * 3) 96 = (-24 + 12x) Solving 96 = -24 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 96 + -12x = -24 + 12x + -12x Combine like terms: 12x + -12x = 0 96 + -12x = -24 + 0 96 + -12x = -24 Add '-96' to each side of the equation. 96 + -96 + -12x = -24 + -96 Combine like terms: 96 + -96 = 0 0 + -12x = -24 + -96 -12x = -24 + -96 Combine like terms: -24 + -96 = -120 -12x = -120 Divide each side by '-12'. x = 10 Simplifying x = 10
| 5(m-4)+6m=5(m+3)-7 | | -10x^2+6x+3=0 | | 2(3x+4)+2x=11x-4+x | | Y=12x^2+24 | | 8x+1=6(1+3x)-2(5x-6) | | 3(2x-7+5x)=x-1 | | F(x)=12x^2+24 | | H=-16t^2+128t+5 | | -6a-36=-4(3a+3) | | 3x+129= | | -7y=-21+28 | | 1/2(x-5)=x-2 | | 4x+3/-5x-3=-1/2 | | 6v-5+5=6v | | (2x^2+6x-7)+(4x^2+2x+17)-(6x^2-11)= | | -4(4-7b)-3(4b-6)=-30 | | 6(x-2)-2x=-40 | | -147=-7(3-3r) | | A=3X(-1) | | 1+5m+7=-7 | | t*-1.5=8 | | -4*-1.5=6 | | -8(p-5)=109.6 | | 4-3x=4(3-x)-3x | | -0.1875*8=-1.5 | | (x^2+5x+5)-(5x^2-8x+7)= | | 8*t=-1.5 | | -4.45-2=-5.5s-4.2 | | -7k-5(-7k+7)=-3+4(7-8k) | | 6*t=-9 | | 6*(-9)=t | | -(h+7)=-8 |